Occupancy of the iron binding sites of human transferrin. - Huebers, H A (1984)
The in vivo distribution of iron between the binding sites of transferrin was examined. Plasma was obtained from normal subjects under basal conditions and after in vitro and in vivo iron loading. Independent methods, including measurement of the transferrin profile after isoelectric focusing and cross immunoelectrophoresis, and determination of the iron content in the separated fractions were in agreement that there was a random distribution of iron on binding sites. This held true with in vitro loading, when iron was increased by intestinal absorption and with loading from the reticuloendothelial system. The data indicate that the distribution of apo-, monoferric, and diferric transferrins is predictable on the basis of the plasma transferrin saturation and negate the concept that iron loading of transferrin in vitro is a selective process with possible functional consequences in tissue iron delivery.